Efeitos farmacológicos da Esculina em modelos animais de lesão gástrica e possíveis mecanismos envolvidos - Rios, Emiliano Ricardo Vasconcelos (2009)
Ulcer can be defined as a chronic inflammatory disease of the stomach and duodenum, which appears as a lesion in the digestive tract, which extends through the mucosa muscle or more deeply. The ulcer usually occurs because of an imbalance between protective and agrssive factors of the mucosa. Esculin (ESC) (6.7-Dihydroxycoumarin-6-O-Glucoside) was evaluated in models ethanol or indomethacin-induced gastric lesions in mice. Esculin (12.5, 25 and 50 mg/kg, p.o.) significantly reduced gastric lesions induced by absolute ethanol (0.2 mL/animal) at 69.96, 72.94 and 79.33% respectively, showing no relationship dose-response at the doses studied. This gastroprotection was also evaluated microscopically showing that the ESC (25 mg/kg, p.o.) decreased the cell loss in the mucosa, submucosal edema and hemorrhage. Esculin (25 and 50 mg/kg, p.o.) also reduced significantly the gastric lesions induced by indomethacin (20 mg/kg, p.o.). Gastroprotective mechanism of ESC was examined in the dose of 25 mg/kg, in the model of gastric lesions induced by ethanol in mice. In animals pretreated with L-NAME (10 mg/kg, sc), an inhibitor of nitric oxide synthase, or with glibenclamide (5 mg/kg, i.p.), a drug that blocks ATP-dependent potassium channels, or indomethacin (10 mg/kg, p.o.), a nonselective inhibitor of cyclooxygenase, the gastroprotective effect of ESC was inhibited significantly, suggesting the involvement, at least in part, of nitric oxide, activation of potassium channels and endogenous prostaglandins in gastroprotective effect of ESC. Otherwise, the gastroprotective effect of ESC (25 mg/kg, p.o.) was not reversed in animals pretreated with capsazepine (5 mg/kg, i.p.), an antagonist of vanilloid receptor TRPV-1, demonstrating that there is activation of these receptors in the mechanism of action of ESC. This work was also evaluated the antioxidant mechanism of ESC as gastroprotective agent, against ethanol-induced lesions. Under our experimental conditions, the model of induction of ethanol injury caused changes in the antioxidant system of the gastric mucosa of mice as the decrease in the levels of sulfhydryl groups (GSH) and activity of superoxide dismutase (SOD), also showed increased activity catalase (CAT), the activity of myeloperoxidase (MPO) and the concentration of species that react with thiobarbituric acid (TBARS) as index of lipid peroxidation (LPO). Esculin in the model of ethanol did not interfere with the concentration of GSH, but increased SOD activity, allowed the restoration of normal CAT activity, normal levels of LPO and MPO activity. The data suggest that the ESC promotes gastroprotection against gastric lesions induced by ethanol or indomethacin in mice whose mechanisms include the involvement of endogenous prostaglandins, nitric oxide, and or, of KATP channels, as well as an antioxidant activity.